2018
DOI: 10.1007/s00191-017-0549-x
|View full text |Cite
|
Sign up to set email alerts
|

All grown up? The fate after 15 years of a quarter of a million UK firms born in 1998

Abstract: The theory of firm growth is in a rather unsatisfactory state. However, the analysis of large firm-level datasets which have become available in recent years allows us to begin building an evidence base which can, in turn, be used to underpin the development of more satisfactory theory. Here we study the 239 thousand UK private sector firms born in 1998 over their first 15 years of life. A first, and quite striking, finding is the extraordinary force of mortality. By age 15, 90% of the UK firms born in 1998 ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Nevertheless, the start-up rate in Denmark is not significantly different than in advanced economies with other levels of unemployment benefits and the survival rate of new firms in Denmark-where about one half are closed within the first 3 years-is similar to findings in other advanced economies (e.g. Coad et al 2013;Anyadike-Danes and Hart 2014). Second, we have no information on the relationship between the founder and the first employee (e.g.…”
Section: Discussionmentioning
confidence: 45%
“…Nevertheless, the start-up rate in Denmark is not significantly different than in advanced economies with other levels of unemployment benefits and the survival rate of new firms in Denmark-where about one half are closed within the first 3 years-is similar to findings in other advanced economies (e.g. Coad et al 2013;Anyadike-Danes and Hart 2014). Second, we have no information on the relationship between the founder and the first employee (e.g.…”
Section: Discussionmentioning
confidence: 45%
“…Therefore, the lack of effective management tools can restrain growth and even cause failure (Greiner ). In growth‐oriented firms, in order to cope with the increased complexity resulting from a greater number of employees, formal policies and practices need to be cultivated if growth is to be sustained (Arthur ). What our results suggest is that the benefits of formalization for performance are likely to be felt mainly in later stages of development.…”
Section: Discussionmentioning
confidence: 99%
“…While there is no common agreement on the exact cutoff point that differentiates emergent ventures from established ones, scholars have relied on firms' survival ability and their economic contribution to distinguish them. For instance, Anyadike‐Danes and Hart () found that two thirds of new firms die within the first five years, and firms' survival chances only improve after that period. Moreover, regarding growth ability, the same authors found that the fastest rates of growth are recorded up to age five as well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anyadike-Danes and Hart (2018) have recently argued that the theory of firm growth is in a rather unsatisfactory state. To summarise, albeit somewhat crudely, one view is that firm growth, certainly in a firm's early years, can be regarded as essentially 'random' (see Coad et al, 2013aCoad et al, , 2013bCoad et al, , 2015.…”
Section: Taking Stock and Looking Forwardmentioning
confidence: 99%